Effects of aluminum on metabolism of reactive oxygen species and reactive nitrogen species in root tips of different Eucalyptus species - Zilong Ouyang; Bing Liu; Tangkan Li; Tiandao Bai; Weichao Teng (BMC Plant Biology)
Abstract On acidified soil, the growth of Eucalyptus is seriously restricted by aluminum (Al) stress. Therefore, breeding Eucalyptus species with excellent Al tolerance, developing the genetic potential of species, and improving tolerance to Al stress are important for the sustainable development of artificial Eucalyptus forests. By observing the occurrence and distribution of the main reactive oxygen species (ROS) and reactive nitrogen species (RNS) in root tips of Eucalyptus seedlings under Al stress, this study analyzed change in the growth and physiological indexes of Eucalyptus seedlings under Al stress. The antioxidant enzymes activities of the root tips of different Eucalyptus species induced by Al stress resulted in different ROS and RNS contents, ultimately resulting in differing degrees of membrane lipid peroxidation. In addition to suppressions of root relative elongation and root activity, the accumulations of soluble sugar, soluble protein, and proline can be used as indicators of Al sensitivity in Eucalyptus species. This may be an important determinant of the differences in Al tolerance among Eucalyptus species. The accumulation of ROS and RNS in the roots of E. grandis and E. tereticornis resulted in severe oxidative and nitrification stress. The tolerance of E. urophylla and E. urophylla × E. grandis to Al stress was stronger than that of E. grandis and E. tereticornis. Differences in Al toxicity tolerance were related to long-term selection of the original habitat of the species; moreover, the Al tolerance was hereditary. Eucalyptus urophylla × E. grandis had stronger Al tolerance than its parents, which is indicative of heterosis. These results provide theoretical support for the breeding of tree species in areas with acidic soil.